Pemberdayaan masyarakat sekolah melalui pendampingan menuju sekolah sehat untuk mendukung budaya mutu SD Kanisius Sengkan Yogyakarta - Yuliasti Eka Purnamaningrum; Yuni Kusmiyati (Poltekkes Kemenkes Yogyakarta, 2020)
Assistance to healthy schools is carried out to support the culture of the quality of Kanisius Sengkan Elementary School. The school environment serves as a place of learning can also be a threat of disease transmission if not managed properly. More than that, school age for children is also a vulnerable period for various diseases. At the stage of school age children 6-12 years children need special attention because at that stage children do a lot of physical activity, can already react to intellectual stimuli, and carry out learning tasks that demand intellectual abilities or cognitive abilities. Health School Programs development is needed as an effort to foster, develop, and improve the ability to live healthy and health status of students. Clean and healthy behavior in school is important. School-age children are children in periods where children are difficult, age is not neat, critical periods for forming habits, group age, age of play, and in the age of play. The evaluation instrument for knowledge outcomes takes the form of a multiple choice written test. Data analysis techniques using descriptive analysis with percentages. Knowledge of clean and healthy behavior includes personal hygiene at school consisting of 7 factors, namely hand washing, nail hygiene, dress hygiene, dental and mouth hygiene, removing trash, and sports.